(untitled) (Journal of Human Sciences, 2026)
Arbitration is an optional, consensual means resorted to by parties to civil and commercial disputes, whether at the local or international level, to settle these disputes outside the courts. Therefore, the researcher will attempt to shed light on this idea, as an alternative means or method to judicial litigation, and to demonstrate its importance due to the advantages it carries that distinguish it from the judiciary. It guarantees the freedom of contracting through an arbitration agreement between the concerned parties to submit their dispute to an arbitrator or arbitration panel to decide it. It is in contrast to the official judiciary, which is directly supervised by the state, where the parties to the arbitration are responsible for choosing the arbitrator or arbitration panel and determining their powers and the law that governs them, due to their desire to resolve the dispute away from the jurisdiction of the official judiciary and its complex and slow procedures. The main problem that this modest research addresses is represented in the practical problems raised by this method, whether in terms of the nature of its system, or the satisfaction in arbitration, which may be tainted by error or confusion with another means of resolving disputes, as well as the extent to which it can be resorted to in all civil and commercial disputes, or whether it is applied to specific disputes.